2022
DOI: 10.52547/ijimes.2.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Success Factors of Small and Medium Enterprises (SMEs): A Study in Iranian Context

Abstract: This study aims to identify and analyze the success factors of small and medium-sized enterprises (SMEs) following the lines of dynamic capabilities and resources-based views. Methodology: To achieve this objective, the multiple case study method was followed, where 20 SMEs/cases in Iran were selected. For this purpose, the statistical population of the research is the managers, experts and experts of small and medium-sized enterprises. For determining the sample size, a targeted sampling method has been used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
2
0
2
Order By: Relevance
“…Also, the study of Kalita (2018) on educational SMEs in Estonia concluded that both Estonian and Russian speaking respondents reported the importance of the personality, experience and management skills of the owner/manager for their success. Furthermore, management skills and leadership of the owner/manager was reported to be critical for business success of Iranian SMEs (Samadzad and Hashemi, 2022). The results of Benzing et al (2009) as well as Douglas et al (2017) also supported these findings.…”
Section: Research Findings Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Also, the study of Kalita (2018) on educational SMEs in Estonia concluded that both Estonian and Russian speaking respondents reported the importance of the personality, experience and management skills of the owner/manager for their success. Furthermore, management skills and leadership of the owner/manager was reported to be critical for business success of Iranian SMEs (Samadzad and Hashemi, 2022). The results of Benzing et al (2009) as well as Douglas et al (2017) also supported these findings.…”
Section: Research Findings Discussionsupporting
confidence: 53%
“…A wide range of entrepreneur related factors was covered in literatures, this may include owner's/manager's age, and gender (Lampadarios, 2015;Lampadarios, 2016;Li & Eriksson, 2012;Sefiani, 2013), personality traits and leadership capabilities (Samadzad & Hashemi, 2022;Lampadarios, 2015;Okoli et al, 2020;Li, 2019;Li and Eriksson, 2012), entrepreneurial orientation (Lampadarios, 2015;Okoli et al, 2020;Rodrigues et al, 2021), management skills and experiences (Samadzad & Hashemi, 2022;Lampadarios, 2015;Lampadarios, 2016;Li and Eriksson, 2012;Benzing & Chu, 2012;Sefiani, 2013), level of education (Samadzad & Hashemi, 2022;Lampadarios, 2015;Li & Eriksson, 2012;Sefiani, 2013;Benzing et al, 2009), family support and self-employment background (Li, 2019;Benzing & Chu, 2012;Benzing et al, 2009), internal or external locus of control (Samadzad & Hashemi, 2022;Sefiani, 2013), propensity of risk taking (Sefiani, 2013), innovation (Li, 2019), and his/her reputation for honesty and ethics (Benzing & Chu, 2012;Benzing et al, 2009;Dzomonda & Fatoki, 2017). Even though MSMEs' success factors were studied in many previous research, it is unsuitable to standardize a set of factors since many cultural, political, economic, and other business environment differences influence the appreciation of these factors (Benzing &amp...…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Furthermore, SMEs are pivotal in employment generation, enhancing regional economic stability, and promoting effective resource utilization for economic development (Al-Haddad et al, 2019;Samadzad & Hashemi, 2022;Oladimeji et al, 2021). They are recognized for their importance in economic and social roles globally (Matejun & Szczepańczyk, 2013).…”
Section: Job Creation and Economic Diversification 1 Entrepreneurship...mentioning
confidence: 99%
“…Пример еще одной работы этого направления -статья S. Samadzad и M. Hashemi, где на основе анализа 20 кейсов ранжи рованы факторы успеха иранских МСП. Важнейшими признаны бизнес-среда, доступность капитала и государственная поддержка [8]. Стейкхолдерский подход к анализу процессов деятельности МСП в ИРИ реализован A. Jalali et al В исследовании идет речь о положительных косвенных связях между организацией и заинтересованными сторонами за счет новаторства и готовности идти на риск [9].…”
Section: Economics and Management: Theory And Pr Acticeunclassified
“…8 . Использованы материалы Портала данных Ирана 9 -основной мировой базы данных социально-экономической информации по ИРИ, которую ведут Совет по исследованиям в области социальных наук, Принстонский университет и Сиракузский университет (США).…”
unclassified